Arthropod diversity associated with Bt and conventional cotton (Gossypium hirsutum L.) in Colombia - Pérez García, Karol (Revista Mexicana de Ciencias Agrícolas, 2017)
The use of genetically modified organisms (GMOs)  has generated great expectations in the development of  agro-crops. However, uncertainties arise about causal  effects on the beneficial arthropofauna associated  with the cotton crop. In this research the diversity of  associated arthropofauna to the Bt cotton and conventional  agroecosistema in the department of Córdoba-Colombia,  in the cotton growing season 2013-2014, from October  to March was evaluated. Arthropods were collected using  five sampling methods according to the microhabitat; 23  787 individuals were collected, with a total of 240 taxa  grouped into 25 species and 215 morphospecies; the most  abundant order was Hemiptera and Coleoptera was the  richer one. The diversity in both crops was similar with  a richness of 0D= 240 for conventional and 0D= 233 for  transgenic, alpha diversity for conventional was 1D= 36.39  and for Transgenic 1D= 33.39, regarding beta diversity in  the two cultures it showed a value of 1,013 with q= 0, q=  1 and q= 2 of 1.001, results showed that the arthropods  diversity for transgenic and conventional crops was not  different and no significant differences between both  cultures were shown.
Keywords: Bacillus thuringiensis; agricultural crops; arthropods; GMO; transgenic